O sítio Teotônio e as reminiscências de uma longa história indígena no Alto Rio Madeira - Kater, Thiago (2018)
The archaeological site Teotônio, located on the upper Madeira River, next to the homonymous waterfall submerged by the construction of a dam, is considered in this research as a significant and persistent place. Research indicates the upper Madeira as a special context where, unlike the rest of the Amazon, There are long and continuous human occupations, and wide linguistic and cultural diversity. Human presence dates back to 9,500 years BP at the Teotônio site, making it a microcosm of regional historical processes. This analysis focuses on archaeological ceramic material (dating from 3250 years BP) and the construction of the landscape, and seeks to understand how the indigenous ceramist peoples lived, managed and resignified this place. Finally, taking a regional view, i argue how evidence for continuity at this site could relate to broader temporal and geographical episodes, allowing the elaboration of an indigenous history of long duration.